Assessment of heavy metals in Amaranthus viridis L. from Peninsular Malaysia - Yaacob, Aziran (2021)
Human health risk and phytoremediation of potentially toxic metals (PTMs) in edible vegetables have been widely discussed nowadays. This study aimed to determine the concentrations of six PTMs, namely Cd, Cu, Fe, Ni, Pb, and Zn) in Amaranthus viridis (leaves, stems and roots) collected from 11 sampling sites in Peninsular Malaysia and to assess their human health risk (HHR). Fifteen individuals of A. viridis were analysed from each 11 sampling sites with three replicates. All metal content in plant and soil samples were determined by the atomic absorption spectrophotometer (AAS) iCE 3000 series at the Department of Chemistry of UPM. In general, the metal levels followed the order: roots> stems> leaves. The metal concentrations (μg/g) in the leaves of A. viridis ranged from 0.45 to 2.18 dry weight (dw) (0.05-0.26 wet weight (ww)), from 74.8 to 535 dw (8.97-64.2 ww), 2.02 to 7.45 dw (0.24-0.89 ww), and 65.2 to 521 dw (7.83-62.6 ww), for Cd, Fe, Ni and Zn, respectively. The positive relationships between the metals, the plant parts and the geochemical factions of their habitat topsoils indicated the potential of A. viridis as good a biomonitor of Cd, Fe, Ni, and Pb pollution. With most of the values of BCF> 1.0 and TF> 1.0, thus A. viridis is a very potential phytoextraction agent of Cu, Ni and Zn. Additionally, with most of the values of BCF> 1.0 and TF< 1.0, A. viridis is a very potential phytostabiliser of Cd, Fe, and Pb. The experimental greenhouse findings indicated three points. Firstly, wastewater irrigation could cause the accumulation of Cu and Pb in the different parts of A. viridis, although these two metals did not highly contaminate the wastewater. Secondly, the accumulated metal levels in the different parts of A. viridis after 35 days of the experimental greenhouse study were mainly within the metal ranges found in the field-collected samples. Thirdly, the findings also indicated that A. viridis had the potential to be biomonitors of Cu and Pb. Concerning HHR, the target hazard quotients (THQ) for Cd, Cu, Fe, Pb and Zn in the leaves of A. viridis were all below 1.00, indicating there were no non-carcinogenic risks four metals to consumers, including children and adults. Still, routine monitoring of PTMs in Amaranthus farms is much needed.